Förröjningens påverkan på avverkning med förstagallringsskördare - Sjöqvist, Mattias; Olofsson, Vincent (SLU/School for Forest Management, 2018)
Thinning is a part of a forest management program when some merchantable timber is cut while creating better volume growth and higher quality of remaining stems. One arrangement to make the logging operation more effective in thinning is to pre-clean the stand from undergrowth.